Pengaruh Brand Ambassador Produk Skincare Terhadap Minat Beli Konsumen (Studi Followers Instagram @somethincofficial) - Kurnia Mu'immah, Rahmi; Abidin, Zainal; Ramdhani , Muhamad (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Somethinc Skincare is one of the skincare products produced by a local brand. The company uses a Brand Ambassador to attract more consumers and increase its sales results. The Brand Ambassador chosen by Somethinc is NCT Dream. The NCT Dream Brand Ambassador is expected to influence the general public. This study was conducted to determine whether there is an influence between the NCT Dream Brand Ambassador and Consumer Purchase Interest in Followers of the Instagram Account @somethincofficial. This study uses the Source Credibility Theory which explains that the higher the credibility of a communicator, the easier it is to influence many people. This study uses quantitative research with the Explanatory Survey method with data collection techniques using questionnaires filled out online in the form of a google form distributed to 100 respondents of the Instagram Account Followers @somethincofficial. The results of this study indicate that the influence of the NCT Dream Brand Ambassador on Consumer Purchase Interest of Somethinc Skincare Products on Instagram Followers @somethincofficial obtained a significant value of 0.000 <0.05 so it can be concluded that the variable Influence of the NCT Dream Brand Ambassador (X) has an effect on Consumer Purchase Interest on Instagram Account Followers @somethincofficial